PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA LECTORA INSPIRE12 PADA POKOK BAHASAN KIMIA UNSUR KELAS XII IPA SMA/MA - ', Ristina; ', Herdini; Rery, R. Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research was to develop Learning Media Lectora Inspire 12 on the subject Chemical Elements class XII Science SMA/MA. Research method used is Research and Development with the ADDIE development model consistin of stages Analysis, Design, Development, Implementation, and Evaluation. This research was to develop phase and be continue with a definite tryout. The product resulting from the research is an interactive learning media based on Lectora Inspire 12 on the topic of Chemical Element which is packaged in CD form. Data collect technique by validating Learning Media Lectora Inspire 12 to three people validator (1 media expert and 2 matter experts) and the trials of Learning Media Lectora Inspire 12 had done by users. Limited trial subjects are 20 students from class XII. Data analysis technique was used descriptive average analysis. The research results show score the designing aspects 4,54; pedagogic aspects 4,60; the content aspects 4,63; the ease of use aspects 4,47; pretest-posttest 0,66; and the learners response 4,64. Average score overall validation of Learning Media Lectora Inspire 12 on the chemical elements subject is 4,55 including very valid category and the average score overall response users is 4,64 including very good category and can be used on the chemical elements subject in class XII SMA/MA.Keywords: Learning Media, Lectora Inspire 12, Chemical Elements.